Mitochondrial content is central to nuclear gene expression: Profound implications for human health. (3rd January 2016) - Muir, Rebecca; Diot, Alan; Poulton, Joanna
Abstract : We review a recent paper in Genome Research by Guantes et al. showing that nuclear gene expression is influenced by the bioenergetic status of the mitochondria. The amount of energy that mitochondria make available for gene expression varies considerably. It depends on: the energetic demands of the tissue; the mitochondrial DNA (mtDNA) mutant load; the number of mitochondria; stressors present in the cell. Hence, when failing mitochondria place the cell in energy crisis there are major effects on gene expression affecting the risk of degenerative diseases, cancer and ageing. In 2015 the UK parliament approved a change in the regulation of IVF techniques, allowing "Mitochondrial replacement therapy" to become a reproductive choice for women at risk of transmitting mitochondrial disease to their children. This is the first time that this technique will be available. Therefore understanding the interaction between mitochondria and the nucleus has never been more important. Abstract : The amount of energy that mitochondria can generate affects gene expression by influencing protein production at several stages. Cells with the highest mitochondrial content have energy available to activate chromatin, gene transcription, differential alternative splicing of mRNA transcripts, and ribosome biogenesis. This increases protein synthesis and heterogeneity.